Gambaran Kualitas Tidur Pada Lansia Dengan Hipertensi Di Desa Marga, Kecamatan Marga, Tabanan - S Astiti; I Gede Yudiana Putra (Bali Health Published Journal, 2023)
Background: A non-communicable disease that mostly affects the elderly in Indonesia is cardiovascular disease, which is the biggest cause of death for people aged 65 years and over with a higher number of deaths in developing countries. One of the non-communicable diseases commonly experienced by the elderly in society is hypertension or high blood pressure. Hypertension that occurs in society often causes problems, one of which is sleep quality disturbances. Sleep quality is one of the risk factors for hypertension. Inadequate sleep quality results in physiological and psychological balance disorders. Hypertension can be prevented by controlling risk factors, most of which are behavioral factors in the form of life habits, one of which is sleep quality. The purpose of this study was to describe the quality of sleep in the elderly with hypertension Methods: This study used a descriptive method with a quantitative approach using a questionnaire and the sampling technique used was purposive sampling with a total sample of 61 respondents. Results: The most respondents were 60-74 years old with a total of 50.83%, the most sex was women with 57.4%. The most common sleep quality for the elderly was poor sleep quality at 64%. Conclusion: Most of the sleep quality of elderly with hypertension in Marga Village is poor, where hypertension affects the quality of sleep of the elderly so that it is hoped that the elderly will check their blood pressure regularly and carry out therapy to help stabilize blood pressure so that the quality of sleep can be improved.